Description of Health Extention Services in Moving Implementation of Family Planning Program at Korong Tembok - Nur Ikhlas Muharman; Irmawita Irmawita (Universitas Negeri Padang, 2020)
This research is motivated by the implementation of family planning programs by residents. This is allegedly due to maintaining the cleanliness of the extension services carried out by the Village Midwives. This study aims to describe: (1) extension services; (2) assistance services; and (3) health services for participants who take part in the family planning program in Korean Tembok. This research is descriptive quantitative research. The population in this study was taken by all participants who took part in extension activities as much as 40 people and the sample was taken as much as 75% of the population, namely 30 people using cluster random sampling technique. The data technique used questionnaires while the data collection tools used questionnaire data which were analyzed using descriptive analysis of proportions. The results of this study indicate: 1) village midwife services in the aspect of extension services in driving the implementation of family planning programs look high; 2) village midwife services in the aspect of accompanying services in driving the implementation of family planning programs look high; And 3) village midwife services in the aspect of facility services in driving the implementation of family planning programs to appear higher. The suggestions are researching: 1) it is hoped that the health extension officers can improve the services provided in the implementation of counseling; 2) it is hoped that the members of the community will increase their awareness of health, especially in implementing family planning programs; And 3) it is hoped that other researchers will find and examine other variables related to health education.Keywords: extension services, family planning program, health